Headache in Autoimmune Diseases. Issue 3 (14th February 2014) - John, Seby; Hajj‐Ali, Rula A.
<x xml:space="preserve">Abstract</x> Autoimmune diseases are a group of heterogeneous inflammatory disorders characterized by systemic or localized inflammation, leading to ischemia and tissue destruction. These include disorders like systemic lupus erythematosus and related diseases, systemic vasculitides, and central nervous system (CNS) vasculitis (primary or secondary). Headache is a very common manifestation of CNS involvement of these diseases. Although headache characteristics can be unspecific and often non‐diagnostic, it is important to recognize because headache can be the first manifestation of CNS involvement. Prompt recognition and treatment is necessary not only to treat the headache, but also to help prevent serious neurological sequelae that frequently accompany autoimmune diseases. In this review, we discuss headache associated with autoimmune diseases along with important mimics.